Diagnosis and Management of Post Traumatic Epilepsy - Ramzi, Ali; Hunaifi, Ilsa (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Traumatic brain injury (TBI) is a leading cause of disability and death, particularly among children and young adults, and can result in serious complications such as post-traumatic epilepsy (PTE). PTE develops after TBI and is characterized by recurrent seizures without external triggers, with the risk influenced by the location and severity of the injury. Therefore, the authors raise this topic to help improve diagnostic acuity and highlight the importance of laboratory modalities in diagnosing PTE. The literature search was conducted using Google Scholar with the keywords